Synthesis of Ge/C composites as anodes using glucose as a reductant and carbon source for lithium-ion batteries. Issue 77 (1st August 2016) - Choe, Hui-Seon; Kim, Si-Jin; Kim, Min-Chul; Kim, Da-Mi; Lee, Gyu-Ho; Han, Sand-Beom; Kwak, Da-Hee; Park, Kyung-Won
Abstract : We synthesized Ge/C composites as anodes for use in high performance LIBs via heating a mixture of GeO2 powder and glucose as both a reductant and carbon source at 900 °C under a nitrogen atmosphere. Abstract : Ge-based materials as anodes in lithium ion batteries (LIBs) having a large theoretical reversible capacity are needed to overcome the unstable structural and electrochemical properties and pulverization of the electrodes for high-performance LIBs. Here, we synthesized Ge/C composites as anodes for use in LIBs via heating a mixture of GeO2 powder and glucose as both a reductant and carbon source at 900 °C under a nitrogen atmosphere. The data from X-ray diffraction (XRD), Raman spectroscopy, and transmission electron microscopy (TEM) shows that the as-prepared samples consist of crystalline Ge particles and an amorphous carbon phase. Compared to pure Ge, the Ge/C samples exhibit discharge capacities of ∼627.1 mA h g −1, improved cyclability, and excellent rate properties at a current of 3200 mA g −1 .